Mini review: Studying epigenomic alterations can shed light on coping and adaptive abilities during heat stress in monogastric livestock - Zaccaria, Edoardo; van der Valk, Elianne; Kar, Soumya K.; Rebel, Johanna M. J.; Schokker, Dirkjan (Frontiers in Genetics, 2025)
Epigenomics, a field that studies epigenetic changes on a genome-wide scale, has gained prominence because of its potential to reveal biological mechanisms underlying phenotypes in livestock. Animal production is highly dependent on the interaction between animal genetics, physiology, environment, and management practises. Many of these factors have a bidirectional relationship with the epigenome, as they influence and are influenced by it. This article focuses on the role of epigenetics in the adaptation of livestock to environment, particularly heat stress. Epigenetic changes induced by heat stress have been observed in livestock, resulting in short- and long-term alterations that generally affect production performance and health. Research provides strong evidence that gene expression in livestock is also influenced by epigenetic processes such as DNA methylation, histone modifications, chromatin remodelling, and non-coding RNAs to cope with heat stress. Nutritional interventions are a promising way to mitigate the epigenetic changes induced by heat stress. A better understanding of the molecular mechanisms involved in the regulation of gene expression during heat stress is crucial to identify strategies and interventions that can maintain or even improve the health and productivity of monogastric livestock and adapt their resilience and efficiency to different environmental conditions.